2020
DOI: 10.1080/17461391.2020.1713901
|View full text |Cite
|
Sign up to set email alerts
|

High‐intensity cycling re‐warm up within a very short time‐frame increases the subsequent intermittent sprint performance

Abstract: The 33 distance covered while running at high-speed during a football match was reduced by 34 8.4% during the initial part of the second half compared with the initial part of the first 35 half (Weston et al., 2011). Furthermore, the sprint performance was reduced by 2.4% at 36 the onset of the second half compared with at the onset of the first half (Mohr, Krustrup, 37 Nybo, Nielsen, & Bangsbo, 2004). These reductions resulted from the passive recovery 38 during half-time and have been associated with physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
62
2
18

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(87 citation statements)
references
References 52 publications
(81 reference statements)
5
62
2
18
Order By: Relevance
“…For instance, the core temperature in soccer players after the first half of matches is likely to be 39.0°C (Mohr et al, 2004), although the core temperature after 40 min of intermittent cycling exercise in the previous study was 38.0°C (Yanaoka et al, 2020). In addition, although the previous study assessed cycling sprint performance (Yanaoka et al, 2020), the correlation of sprint performance performed on a cycle ergometer with that performed on the ground is moderate at best (Fitzsimons et al, 1993). Sports-specific field tests need to be developed to enhance the ecological validity, separate to the contextual factors that exist in an actual match.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…For instance, the core temperature in soccer players after the first half of matches is likely to be 39.0°C (Mohr et al, 2004), although the core temperature after 40 min of intermittent cycling exercise in the previous study was 38.0°C (Yanaoka et al, 2020). In addition, although the previous study assessed cycling sprint performance (Yanaoka et al, 2020), the correlation of sprint performance performed on a cycle ergometer with that performed on the ground is moderate at best (Fitzsimons et al, 1993). Sports-specific field tests need to be developed to enhance the ecological validity, separate to the contextual factors that exist in an actual match.…”
Section: Introductionmentioning
confidence: 89%
“…Recent reviews have advocated the use of high-intensity RW if the protocol avoids inducing additional fatigue before the commencement of the second half (Hammami et al, 2018;Silva et al, 2018). Yanaoka et al (2020) reported that cyclingbased RW, irrespective of whether it comprised 1 min at highintensity or 3 min at low-intensity, resulted in increased muscle temperature, oxygen uptake, and muscle activation, resulting in improved intermittent cycling sprint performance compared with seated rest. However, the lack of equipment (i.e., ergometers) in "away" stadiums is a major barrier to the administration of RW (Towlson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations